Rō̜i mư̄ rūam rūam čhai pan fan pen čhing : bon sēnthāng kānrīanrū khō̜n rōngrīan khanāt lek - ʻInthirā Witthayasombūn (ʻOngkān ʻÆkchanʻēt Prathēt Thai, 2015)
Local community participation in education and schools in Thailand.